2011
DOI: 10.3109/09513590.2011.593671
|View full text |Cite
|
Sign up to set email alerts
|

The effect of red clover isoflavone supplementation over vasomotor and menopausal symptoms in postmenopausal women

Abstract: Red clover isoflavone supplementation was more effective than placebo in reducing daily vasomotor frequency and overall menopausal intensity in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 34 publications
0
35
1
6
Order By: Relevance
“…In accordance with the calculation it was necessary for 50 participants to complete the study. Minimal clinically important difference in hot flush frequency was found to be a difference of at least 15% as determined from data published by Lipovac et al (2012)[18]. …”
Section: Methodsmentioning
confidence: 81%
See 2 more Smart Citations
“…In accordance with the calculation it was necessary for 50 participants to complete the study. Minimal clinically important difference in hot flush frequency was found to be a difference of at least 15% as determined from data published by Lipovac et al (2012)[18]. …”
Section: Methodsmentioning
confidence: 81%
“…Bioactive isoflavones from Red Clover (RC) (particularly Biochanin A and Formononetin) show promise as candidates for treatment of menopause symptoms as recent clinical trials have demonstrated beneficial effects against menopausal VMS and show minimal side effects with treatment [1820]. Moreover, the safety profile of these compounds is promising and tested in numerous human trials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some efficacy of red clover extracts in the preventing of vasomotor symptoms was demonstrated in a meta-analysis of 5 clinical trials [5], more recently both lack of effects [6, 7] and favorable effects [8] were reported. The data on the long-term effects on the cardiovascular, breast, endometrial, and urogenital health, as well as bone health, are much scarcer [9].…”
Section: Introductionmentioning
confidence: 99%
“…This effect was equivalent to a 76.9 % reduction in the total Hospital Anxiety and Depression Scale (HADS) score (76 % for anxiety and 78.3 % for depression) and an 80.6 % reduction in the total Zung Self-Rating Depression Scale (SDS) score. They also found that red clover isofl avone supplementation was more effective than placebo in reducing daily vasomotor frequency and overall menopausal intensity in postmenopausal women (Lipovac et al 2012 ). Studies by del Giorno et al ( 2010 ) found that a 12-month treatment of women aged 45-65 years with menopausal symptoms, with a daily dose of 40 mg Trifolium pratense , did not yield a signifi cant improvement in menopausal symptoms and sexual satisfaction.…”
Section: Clinical Studiesmentioning
confidence: 99%